Neutrosophic Copson Type Rough I-Statistical Convergent Sequences - Manpreet Kaur; Reena Antal; Meenakshi Chawla (Pan-American Journal of Mathematics, 2025)
The main objective of work is to study the concept of rough I-statistical convergence for Copson-transformation in the setup of neutrosophic normed spaces by considering algebraic and topological properties of the set of rough ideal statistical limit points for Copson transformation sequences. We also defined the set of rough I-statistical cluster points and investigated some properties for the sequences using Copson-transformation.